ANALISIS EFISIENSI DAN EFEKTIVITAS STANDAR HARGA PERJALANAN DINAS SEKRETARIAT DAERAH KABUPATEN MADIUN - Mahyudin, Ata Royan (Master of Public Administration, Universitas Slamet Riyadi, 2024)
Official travel expenses are various expenses incurred in the context of official travel in connection with duties and functions. Official travel in this case is domestic official travel, namely travel outside the place of residence carried out within the territory of the Republic of Indonesia for the benefit of the state.The aim of this research is to determine the application of price standards in the preparation of work plans and budgets for the Regional Secretariat of Madiun Regency.The method used in this research is a type of qualitative research through presentation and description. The subjects in this research were 8 informant respondents consisting of 6 people from the Regional Secretariat Development Administration Section, Regional Development Planning Agency and Regional Financial and Asset Management Agency, 1 person from the Health Service Planning Section and 1 person from the Public Works and Spatial Planning Department Planning Section. Data collection techniques use interviews (in-depth interviews), Focus Group Discussions (FGD)The level of efficiency of the official travel budget at the Regional Secretariat of Madiun Regency for 2021 - 2022 based on the results of calculations and overall analysis can be assessed as quite efficient, while the level of effectiveness of the official travel budget for 2021 - 2022 shows that the overall results are at an effective level, even close to a very high level. effective. Efforts to implement the efficiency of the official travel budget have been carried out by the Regional Secretariat of Madiun Regency by optimizing the use of the budget as best as possible and maximizing the use of budget originating from the APBD for public service needs to the community as well as preparing program plans for each unit and sector by utilizing information systems so that they are clearer. and measurable in determining program and activity priorities.